Sustainability in Supply Chain Management: The Role of Partner Collaboration and Power - Appiah, Listowel Owusu (International Journal of Management and Sustainability, 2019)
Sustainability issues in supply chain management have been at the front of research and practice owing to concerns about natural resources exhaustion, pollution levels etc. emanating from business activities. Pressures from external entities like government agencies, consumer movements, and NGOs, are driving firms to implement sustainable practices internally and across their supply chains. This study sought to assess how sustainability performance in supply chains can be enhanced through collaboration and power. A total of 104 construction and Manufacturing firms drawn from the Ashanti and Greater Accra regions of Ghana were used in the study. A structured questionnaire was used to collect data from top management members in the respondent organizations. Regression models were employed to test the relationship among the variables. The findings reveal that the quest to avoid sanctions from regulatory bodies, bad publicity in the media and conflict with local communities are the main drivers of sustainability among the firms in the study population. Other external pressures such as NGOs and consumer movements were found to have little effect on the firms in the study. Also, external pressures have significant effect on collaboration and sustainability performance, and that collaboration mediates the relationship between external pressures and sustainability performance. The author calls for a rise in consumer movements to increase the pressure on firms to adopt sustainable practices. Also, regulators must adopt a supply chain approach to enforcing environmental and social laws on firms by charging the powerful, visible firms to take charge of their supply chains.